Policy and Guide for Dealing with Nuclear Disaster Threat in Indonesia - Apriliani, Dewi (Magister Administrasi Publik, 2020)
The research analyzed policies and guidelines for dealing with nuclear disaster threat in Indonesia within a collaborative approach. A case study qualitative method was used to explore and analyze the nuclear disaster threat policy and guidelines in Indonesia. The research was based on LIPI-UNESCO/ ISDR indicators on natural disaster preparedness and IAEA parameters on nuclear emergency preparedness requirements). Results showed that policies and guidelines on dealing with nuclear disaster threat in Indonesia are still deficient (34.1%); and there is no synergy and integration of policies and guidelines on preventing nuclear emergency between nuclear technology users and nuclear energy regulators on one hand and disaster management policies and guidelines at the local and national government level. Thus, enhancing policies and guidelines on dealing with nuclear disaster threats, there is need for National Disaster Management Agency (BNPB) to undertake collaborative governance policies with related ministries/ agencies, facilitate the integration of nuclear hazard regulations into disaster management regulations, and facilitate the establishment of national nuclear disaster management organizations.